Cell-responsive nanogels for anticancer drug delivery - Maciel, Dina Maria Sousa (2015)
One of the main goals in Nanomedicine is to create innovative drug delivery systems (DDS) capable of delivering drugs into a specific location with high efficiency. In the development of DDS, some essential properties are desired, such as biocompatibility and biodegradability. Furthermore, an ideal DDS should be able to deliver a drug in a controlled manner and minimize its side effects. These two objectives are still a challenge for researchers all around the world. Nanogels are an excellent vehicle to use in drug delivery and several other applications due to their biocompatibility. They are polymer-based networks, chemically or physically crosslinked, with at least 80-90% water in their composition. Their properties can be tuned, like the nanogel size, multifunctionality and degradability. Nanogels are capable of carrying in their interior bioactive molecules and deliver them into cells. The main objective of this project was to produce nanogels for the delivery of anticancer drugs with the ability of responding to existent stimuli inside cells (cellresponsiveness nanogels) and/or of controlled drug delivery. The nanogels were mainly based on alginate (AG), a natural biopolymer, and prepared using emulsion approaches. After their synthesis, they were used to encapsulate doxorubicin (Dox) which was chosen as a model drug. In the first part of the experimental work, disulfide-linked AG nanogels were prepared and, as expected, were redox-sensitive to a reducing environment like the intracellular medium. In the second part, AG nanogels crosslinked with both calcium ions and cationic poly(amidoamine) dendrimers were developed with improved sustained drug delivery. The prepared nanogels were characterized in terms of size, chemical composition, morphology, and drug delivery behavior (under redox/pH stimuli). The in vitro cytotoxicity of the nanogels was also tested against CAL-72 cells (an osteosarcoma cell line).